Experimental Investigation of the Effects of Partially Hydrolyzed Polyacrylamide (PHPA) and Xanthan on Foam Stability - Afrouz, Mohammadreza (Machines Review, 2019)
Foam flooding is one of the enhanced oil recovery (EOR) methods. Stability of the produced foam plays a significant role in overall efficiency of foam flooding. Polymers can be added to foam solutions to improve foam stability and enhance its characteristics. In this study the feasibility of improving foam stability by polymer addition is investigated. Alkyl Ethoxy Sulfate (AES) surfactant as the anionic surfactant and Cetyl Trimethyl Ammonium Bromide (CTAB) as the cationic surfactant are used as the foaming agents. The effects of polymer addition on foam stability is determined by the addition of different concentrations (0-3000 ppm) of PHPA and xanthan to foam solution and finally foam stability as the time taken for 80% of the foam to collapse was determined accordingly. The experimental results showed that CTAB performed better than AES as the foaming agent. Foam stability was enhanced by the addition of both PHPA and xanthan to foam solutions. Xanthan was more compatible with formation brine and PHPA was more compatible with fresh water to enhance foam stability.